Comparison of hot water and alkaline pre-treatments on the properties of wheat straw NSSC pulp - Soodeh Zhand (تحقیقات علوم چوب و کاغذ ایران, 2014)
The purpose of this study was to compare the properties of wheat straw (Zagros sp) collected in Golestan province NSSC pulp under alkaline pretreatment with 1% sodium hydroxide and boiling pretreatment. Wheat Straw pretreatment with 1% sodium hydroxide and hot water at water to straw ration of 10 to 1 was conducted at 70ْC for half an hour. NSSC pulping was carried out at constant pulping condition including liquor to straw ratio of 5:1, maximum temperature at 160ºC for 30 minutes. In order to study the effect of sodium hydroxide on strength properties of paper in some cases only Na2S03 was used. After pulping, defibration was carried out by laboratory refiner to reach 380±25ml (CSF). Sixty gram/m² hand sheets were prepared from each pulp. The strength properties were determined according to TAPPI standard. Results showed that with the exception of RCT strength, pretreatment had significant effect on increasing the strength properties of papers and by alkaline pretreatment, brightness of the pulps decreased and tensile strength, burst strength, breaking length, stiffness and density increased. Using chemical pretreatment especially sodium hydroxide resulted in reduction in yield and brightness level and improvement in strength of the pulps.